Respuesta :

Answer:

It is proved that  [tex]6\cos ^{2}x -3 = 3 - 6\sin ^{2} x[/tex] .

Step-by-step explanation:

We already have the identity of x as [tex]\sin ^{2}x + \cos ^{2}x = 1[/tex] .......... (1)  .

So, from equation (1) we can write that

[tex]\cos ^{2} x = 1 - \sin ^{2} x[/tex]

⇒ [tex]6\cos ^{2} x = 6 - 6 \sin ^{2} x[/tex]

⇒ [tex]6\cos ^{2} x -3 = 6 - 6 \sin ^{2}x -3[/tex]

[tex]6\cos ^{2}x -3 = 3 - 6\sin ^{2} x[/tex]

Hence, it is proved that  [tex]6\cos ^{2}x -3 = 3 - 6\sin ^{2} x[/tex] . (Answer)